The Role of Individual Risk Attitudes on Old Wine Valuations. (November 2019) - Georgantzís, Nikolaos; Tisserand, Jean-Christian
Abstract: In this article, we report the results of an experiment designed to address the effect of risk attitudes on valuations of aged wines. We find that higher risk taking in the economic domain is associated with a significantly higher willingness to pay for an old wine. Given the increasing interest of consumers and investors in old wines, our results are applicable to the pricing of old wines and to the use of auctions as an efficient willingness to pay elicitation mechanism. (JEL Classifications: C91, D44, L66)